Mechanisms of a Mycobacterium tuberculosis active peptide - Rao, Komal Umashankar (2023)
Multidrug-resistant tuberculosis (MDR) continues to pose a threat to public health. Previously, we identified a cationic host defense peptide with activity against Mycobacterium tuberculosis in vivo and with a bactericidal effect against MDR M. tuberculosis at therapeutic concentrations. To understand the mechanisms of this peptide, we investigated its interactions with live M. tuberculosis and liposomes as a model. Peptide interactions with M. tuberculosis inner membranes induced tube-shaped membranous structures and massive vesicle formation, thus leading to bubbling cell death and ghost cell formation. Liposomal studies revealed that peptide insertion into inner membranes induced changes in the peptides' secondary structure and that the membranes were pulled such that they aggregated without permeabilization, suggesting that the peptide has a strong inner membrane affinity. Finally, the peptide targeted essential proteins in M. tuberculosis, such as 60 kDa chaperonins and elongation factor Tu, that are involved in mycolic acid synthesis and protein folding, which had an impact on bacterial proliferation. The observed multifaceted targeting provides additional support for the therapeutic potential of this peptide.